Profile of The Use of Prophilacic Antibiotics in Heart Surgery Patients - Jenny Pontoan; Okpri Meila; Alisyah Riefla Indriyani (CV. Ulil Albab Corp, 2023)
Coronary Artery Bypass Graft (CABG) is a surgical procedure that aims to remove blocked coronary arteries and maximize blood vessel flow. Heart valve surgery is a treatment option recommended by doctors to prevent complications from occurring more severe to the heart with the main indication of valve stenosis and regurgitation. For the use of prophylactic antibiotics, studies have shown that prophylactic antibiotics with first- and second-generation cephalosporins can effectively reduce the incidence of surgical wound infection and postoperative infectious complications in cardiac surgery patients. This study aims to determine the use of prophylactic antibiotics in cardiac surgery patients. This research uses descriptive research type with retrospective data collection cross-sectional, by collecting secondary data derived from medical records of cardiac surgery patients who used prophylactic antibiotics and met the study inclusion criteria. The results showed that the majority of the prophylactic antibiotics Cefuroxime in 317 patients (88.06%) consisted of 206 patients (57.2%) and 111 patients (30.8%) of patented Cefuroxime. The majority of preoperative length of stay ≤ 1 day 331 patients (91.9%), and there was no incidence of surgical wound infection in the whole sample (100%). Based on the results of the study, it can be concluded that the most use of prophylactic antibiotics is Cefuroxime